User Perception and Preferences in Dynamic Ridesharing Platforms - Bashir, Ribadu Rukkaiyatu; Mathew, Odekunle Remilekun; Atte, Momoh Abdulfatai; Samson, Onanaye Adeniyi (Darul Yasin Al Sys, 2025)
This study investigates user perceptions and preferences regarding dynamic ridesharing services, with the objective of integrating behavioral insights into the design of more user-centric mobility platforms. A questionnaire-based survey was conducted to collect both quantitative and qualitative data from potential ridesharing users, focusing on expectations, preferred features, willingness to tolerate trade-offs such as longer travel times or detours, and key deterrents to adoption. Results indicate a strong willingness to share rides for cost savings and environmental benefits, while highlighting safety, affordability, and travel efficiency as the most valued attributes. Conversely, fear of harassment and concerns about excessive detours or wait times were identified as the main barriers to adoption. The study concludes that effective ridesharing platforms must prioritize user safety, ensure efficient routing, and maintain competitive pricing to enhance user experience and encourage widespread acceptance of dynamic ridesharing solutions.